A Case Report of Typhoidal Acute Acalculous Cholecystitis - Neeha Rajan; Imeldah Motoroko; Dilshan Udayasiri; Jo-Lyn McKenzie; Jason S. C. Tan; Adrian R. Tramontana (Case Reports in Infectious Diseases)
Introduction. Acalculous cholecystitis in the setting of typhoid fever in adults is an infrequent clinical encounter, reported sparsely in the literature. In this case report we review the presentation and management of enteric fever involving the biliary system and consider the literature surrounding this topic. The aim of this case report is to alert clinicians to the potential diagnosis of extraintestinal complications in the setting of typhoid fever in the returned traveller, requiring surgical intervention. Presentation of Case. We report the case of a 23-year-old woman with acalculous cholecystitis secondary to Salmonella Typhi. Discussion. There is scarce evidence surrounding the optimal treatment and prognosis of typhoidal acalculous cholecystitis. In the current case, surgical invention was favoured due to failure of medical management. Conclusion. Clinical judgement dictated surgical intervention in this case of typhoidal acute acalculous cholecystitis, and cholecystectomy was safely performed.